Au Maghreb un contre-pouvoir du côté des femmes : l'enfant endormi dans le ventre de sa mère - Colin, Joël (L'Année sociologique, 2003)
In Maghreb, in the everyday life as well as in the law, equality between men and women was not much sought-after : until a recent period, differentiation of the roles and of the status according to the sex looked equitable.
Keywords: Moeurs et coutumes -- Djerba

La période de ḥasūm à Djerba: la fête des êtres de l’Au-delà sur terre - Földessy, Edina (Arabist Budapest Studies in Arabic, 2003)
Keywords: Croyances populaires -- Djerba; Moeurs et coutumes -- Djerba